Ferric ion detection mechanism of a dicarboxylic cellulose nanocrystal and a 7-amino-4-methylcoumarin based fluorescent chemosensor. Issue 26 (7th June 2022) - Sun, Xiaozheng; Li, Jianye; He, Qiang; Xue, Yanhua; Bai, Yu; Yang, Yuyao; Wang, Xiaogang; Wang, Sun; Li, Rui
Abstract : As one of Earth's most widely distributed and abundant elements, iron impacts the natural environment and biological systems. Abstract : As one of Earth's most widely distributed and abundant elements, iron impacts the natural environment and biological systems. Therefore, developing a simple, rapid, and accurate Fe 3+ detection method is vital. Fluorescent dicarboxylic cellulose nanocrystals (FDCN) with selective quenching of Fe 3+ were synthesized using 7-amino-4-methylcoumarin (AMC), and dicarboxylic cellulose nanocrystals (DCN) prepared by sequential periodate–chlorite oxidation. The sensing characteristics and detection mechanism of FDCN for Fe 3+ were studied by fluorescence spectrophotometry, Fourier-transform infrared spectroscopy (FTIR), the Stern–Volmer equation, Job's plot method, and the Benesi–Hildebrand equation. The results showed that FDCN was highly selective for Fe 3+, and other metal ions did not reduce the selectivity. High sensitivity with a detection limit of 0.26 μM and a Stern–Volmer quenching constant of 0.1229 were also achieved. The coordination between Fe 3+ and the carboxylic, hydroxyl, and amide groups on the surface of FDCN and the carbonyl of coumarin lactones to form FDCN/Fe 3+ complexes prevented the intramolecular charge transfer (ICT) process and led to the fluorescence quenching of FDCN. EDTA restored the fluorescence emission of quenched FDCN. The complexation stoichiometry of Fe 3+ to FDCN was 1 : 1, and the association constant was 3.23 × 10 4 M −1 . The high hydrophilicity, sensitivity, and selectivity of FDCN for Fe 3+ make the chemosensor suitable for Fe 3+ trace detection in drinking water and biology.